Pengaruh Korupsi terhadap Investasi dan Pertumbuhan Ekonomi di Negara Berkembang - Siregar, Friska Anggi; Fitria, Nayya; Yulis, Sari (Locus Journal of Academic Literature Review, 2025)
Corruption is a key structural barrier to economic growth and investment flows in developing countries. This study analyzes a range of academic literature, international reports, and empirical cases from countries such as Mali, Ethiopia, and Indonesia to examine how corruption affects investment efficiency, public budget management, infrastructure quality, and socio- economic inequality. The synthesis reveals that corruption increases transaction costs for investors, creates legal uncertainty, and distorts policy-making and budget allocation. Moreover, it worsens wealth distribution and undermines public services such as education and healthcare, thereby limiting investment in human capital. The study further emphasizes that the impact of corruption is not uniform, but highly dependent on the strength of institutional governance. Therefore, institutional reform, enhanced transparency, and stronger public oversight are essential prerequisites for fostering inclusive and sustainable economic development.